Effectiveness Of Incision Wound Healing Of Pandanus Amaryllifolius Roxb In Wistar Rats - Muna Soraya Putri; Ermi Girsang; Linda Chiuman; Chrismis Novalinda Ginting (International Journal of Health and Pharmaceutical (IJHP), 2022)
The incision is a condition of tissue discontinuity that is commonly encountered with the risk of prolonged healing time, imperfect wound healing, infection, etc. Assessment of the wound healing activity of the incision is the purpose of this research, which includes an examination of wound contraction, the thickness of collagen fibers, and the number of new blood vessels formation. In total, 25 rats will be divided into 5 test groups, each consisting of 5 rats; the control group (cream base treated), standard group (Povidone Iodine), followed by the treated group with 10%, 20%, and 30% pandan leaf extract ointment. The preliminary screening of phytochemical analysisshowed the presence of alkaloids, saponins, flavonoids, tannins, triterpenoids, and steroids and glycosides, with the total content of phenols and flavonoids from the ethanolic extract of Pandan Wangi is 20.95 GAE mg/gram extract, and 23.57 TAE mg/gram extract. Wound contraction examination result showed a significant difference between the treatment groups on day 16 and a sign the pairs of groups after being given the ointment with each concentration (p <0.05), especially in the group with 30% fragrant leaves extract and the standard group. Examination of new blood vessels showed a significant difference (p <0.05), especially with 30% of the leaves extract ointment. There was also a significant difference in collagen density in the group given pandanus ethanol ointment, especially at the 30% pandanus extract content against the group that was only given the ointment base. This research strongly suggests that the fragrant pandan leaf extract ointment is effective in healing incisional wounds and promises the potential for further studies on the pharmacological aspects.